2019
DOI: 10.1088/1755-1315/272/3/032134
|View full text |Cite
|
Sign up to set email alerts
|

Methodical Toolkit of Portfolio Management of Services of Professional Education

Abstract: The article forms the author’s methodical toolkit for managing the portfolio of the professional education services, as well as the results of its application. To manage the portfolio of the professional education services it is proposed to analyse them in order to identify the most promising areas of activity of the higher education establishments in the market of the educational services. It is proposed to monitor the higher education establishments on the basis of the creation of the n-dimensional matrices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, scholars from around the world are exploring issues of education and improving its quality, namely: − digital education [4], − a model of a different higher education [5], − digital security [6], − distance learning system [7], − portfolio of vocational education services [8], etc. Having studied the educational direction, the researchers have concluded that there is no formed, recommended structure for the work of educational and methodological support of the educational organization (listeners, teaching employees).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, scholars from around the world are exploring issues of education and improving its quality, namely: − digital education [4], − a model of a different higher education [5], − digital security [6], − distance learning system [7], − portfolio of vocational education services [8], etc. Having studied the educational direction, the researchers have concluded that there is no formed, recommended structure for the work of educational and methodological support of the educational organization (listeners, teaching employees).…”
Section: Methodsmentioning
confidence: 99%